Mechanism of Organic Matter Accumulation in Black Shales of the Yuertusi Formation in the Tarim Basin: Insights From Paleoenvironmental Variation During the Early Cambrian - Wang, Yangyang; Chen, Jianfa; Shen, Weibing; Li, Min (Frontiers in Earth Science, 2022)
The paleo-environment during the Early Cambrian is closely related to the accumulation mechanism of organic matter (OM) from the Lower Cambrian black shales. However, its paleo-environment remain a controversial issue. Here, we reported a lot of detailed data of sedimentary stratigraphy and geochemistry of the Lower Cambrian Yuertusi Formation in Aksu area, Tarim Basin. The Yuertusi Formation from Yutixi outcrop consists mainly of silicalite at the base, two sets of black shales, and crystalline dolostone. Based on the redox conditions traced by U/Th, V/Cr, Ni/Co and V/Sc, the hydrothermal activity traced by Ce/Ce*, Cr/Zr, U/Th, Fe/Ti and (Fe+Mn)/Ti ratios, as well as paleo-productivity traced by Ba, Cu, Rb/Sr and other parameters, it showed that there were variations in the depositional environments of the Yuertusi Formation: (1) the silicalite at the base were deposited under an euxinic condition and intense hydrothermal activity. Mo-U co-variation analysis revealed that the north margin of Tarim Basin belonged to the unrestricted marine during the Early Cambrian; (2) the lower black shales were deposited under an oxygen-poor condition and weak hydrothermal activity; and (3) the upper black shales were deposited under oxygen-poor and sub-oxic conditions and almost no hydrothermal activity. Although the hydrothermal activity improved paleo-productivity, the TOC values were low on the whole, which may be due to the intense hydrothermal activity that damaged the formation of source rocks. Comprehensive studies showed a gradually oxidizing environment and weakening paleo-productivity during the Yuertusi Formation deposited. The anoxic conditions were conducive to the preservation of OM, and the high-quality source rocks represented by the black shales of the Yuertusi Formation were formed, especially the first set of black shales. However, the enrichment of OM may be affected by the intense hydrothermal activity.